Answer:
x = -5
y = -4
Explanation:
Given,
y = -1/5 x - 5 ......... (i)
y = 2/5 x - 2 ......... (ii)
From equation (i), we get,
y = -1/5 x - 5
y = -x/5 - 5
y = (-x-25)/5 (Since the L.C.M is 5) ............ (iii)
Putting y = (-x-25)/5 in equation (ii),
y = 2/5 x - 2
or, (-x-25)/5 = 2/5 x - 2
or, (-x-25)/5 = 2x/5 - 2
or, (-x-25)/5 = (2x-10)/5
or, -x-25 = 2x - 10 (multiplying both the sides by 5)
or, -x - 2x = 25 - 10
or, -3x = 15
or, x = -(15/3) = -5
Putting the value of x in equation (iii), we will get,
y = (-x-25)/5
or, y = (5-25)/5
or, y = -20/5
or, y = -4
Then solution is x = -5 and y = -4